ANALISIS ROA DAN DER DALAM MEMPREDIKSI POTENSI FINANCIAL DISTRESS PADA PERUSAHAAN BATU BARA DI TENGAH FLUKTUASI HARGA KOMODITAS ( TAHUN 2020-2024) - Muhammad Rijalul Abror Al-Ma’ruf (MANAJEMEN DEWANTARA, 2026)
This research aims to analyze the influence of Return on Assets (ROA) and Debt to Equity Ratio (DER) in predicting potential financial distress in coal mining companies listed on the Indonesia Stock Exchange. The study specifically focuses on the transformative period of 2020-2024, which was characterized by global economic shocks and extreme commodity price fluctuations. The research employs a quantitative approach using secondary data from audited annual financial statements. Purposive sampling was used to select representative coal companies that remained active throughout the observation period. Data analysis was conducted using Multiple Linear Regression via SPSS software, incorporating classical assumption tests and hypothesis testing through t-tests and F-tests. Potential financial distress is measured using the modified Altman Z-Score model. The results indicate that ROA has a significant positive effect on the Z-Score, suggesting that higher profitability effectively reduces the risk of financial distress. Conversely, DER does not show a significant partial effect on the Z-Score in this specific sector. Collectively, ROA and DER significantly influence financial distress potential, although the adjusted R-square of 0.179 implies that external macro factors predominantly drive the financial health of coal companies during this volatile period.